The Effects of Glycerl Trinitrate and Adenosine 5-Triphosphate On Activation of Potassium Channel-Mediated Vasorelaxation in Female Rats Aortic Smooth Muscle - Al-Habib, Omar A.M.; Mohammed, Chinar M. (Science Journal of University of Zakho, 2016)
Nitric oxide (NO) is produced from virtually all cell types composing the cardiovascular tissue and regulates vascular function through fine regulation of excitation–contraction coupling. Endogenous metabolites play a major role in coronary autoregulation. Therefore, the aim of the present study is to investigate the contribution of Glyceryl trinitrate (GTN) and Adenosine 5-triphosphate (ATP) mediated relaxation in rat aortic smooth muscle in intact and endothelium denuded endothelium rings precontracted with Phenylephrine (PE). The thoracic aorta was isolated, cut into rings, and mounted in organ-bath chambers and isometric tension was recorded using PowerLab Data Acquisition System (Model ML 870). The results showed that GTN as NO donor produced dose-dependent relaxation in intact aortic rings precontracted with PE (1 µM) that disinhibited in the presence of Glibenclamide (GLIB), while GLIB attenuate the response induced by ATP in intact aortic rings. L-nitroarginine methylester (L-NAME) an antagonist for nitric oxide synthases (NOS), not abolish the response induced by GTN (Emax 55.28% ± 0.18). Caffeine, ATP receptors antagonist, were partially inhibit the relaxation induced by ATP (vasodilation rate decreased by about 20.57 %). In endothelium denuded aortic rings, vasorelaxation induced by ATP were significantly attenuated, while GTN significantly increased relaxation by removing endothelium. These results suggested that (1) ATP-dependent potassium channel did not involve in GTN inducing vasorelaxation while KATP and A2B receptors have a role in ATP mediated vasorelation (2) ATP partially dependent on endothelium in contrast to NO donors that independent to endothelium.
Keywords: Nitric oxide; Glyceryl trinitrate; Adenosine triphosphat; Potassium channels; Aorta